Manufacturing of composites - Loos, A. C. (Alfred C.); Hyer, M. W.; American Society for Composites (Lancaster, PA : Destech Publications Inc., 2013)
'Book comprises 16 original papers on the processing and manufacturing of thermoset and thermoplastic composites. Nine chapters cover modeling and process parameters for many shapes of thermosets using RTM, VARTM and CRTM. Five chapters focus on thermoplastics, including FEM analysis, preforms, and optimizing manufacturing. The book concludes with important chapters on new processes, such as vacuum-bag-only prepregs (VBO) for out-of-autoclave (OOA) fabrication of aerospace composites.'--Publisher description.
Evaluation of temperature profiles in thick composite parts during autoclave processing / T. Shimizu, J.C. Kotlik, A.R.A. Arafath, and A. Poursartip -- Process monitoring for large-scale composite structures by optical-fiber-based distributed sensing system / Y. Ito, K. Fujimoto, S. Minakuchi, T. Mizutani, N. Takeda, H. Koinuma, and T. Shimizu -- Spring-in, twist & bowling : experimental assessment and modelling of process induced stresses and distortions in composite laminates / T. Garstka, K.D. Potter and M.R. Wisnom -- Filament winding : analytical kinematic solutions and collision control / S. Koussios and O.K. Bergsma -- Wetout of high pull speed resin injection pultrusion for tapered injection chamber with multiple injection ports / A.L. Jeswami, J.A. Roux and J.G. Vaughan -- An experimental investigation of the VARTM infiltration process / B.W. Grimsley, R.J. Cano and A.C. Loos -- A new model for the VARTM process including progressive saturation effects / J. Bayldon and I.M. Daniel -- RTM process simulation and optimization of composite fan blades reinforced by 3D woven fabrics / F. Trochu, C. Demaria, E. Ruiz, B. Dambrine and T. Godon -- The compression resin transfer molding process for automotive composite components / J.M. Lawrence, P. Simacek and S.G. Advani -- Thermostamping of woven commingled glass-polypropylene composite fabrics : FEA with user-defined subroutines in ABAQUS / J. Gorczyca, J. Sherwood and J. Chen -- Finite element simulation for textile composite stamping / X. Peng, F. Ding and J. Cao -- Manufacturing of braided thermoplastic composites with carbon/nylon comingled fibers / L. Laberge-Lebel and S. Van Hoa -- Study of compressibility and resin flow in the development of thermoplastic matrix composite laminates by film stacking technique / G.S. Agarwal, G. Reyes and P.K. Mallick -- Automated fibre placement (AFP) of aerospace composite structures / M. Hojjati, J. Chen, A. Yousefpour, and M.-A. Octeau -- Moisture and pressure effects on void formation in prepreg processed composites / L. Grunenfelder and S. Nutt -- The effect of material and process parameters on tow impregnation and micro-void formation in out-of-autoclave prepregs / T. Centea and P. Hubert.
Includes bibliographical references and index.
Keywords: Composite materials -- Testing; Composite materials -- Manufacturing